Indocyanine Green Aided Schlemm Canal Identification During Gonioscopic Assisted Transluminal Trabeculotomy. Issue 8 (6th August 2022) - Panigrahi, Arnav; Huang, Alex S.; Arora, Monika; Kumari, Somya; Mahalingam, Karthikeyan; Gupta, Viney; Gupta, Shikha
Abstract : Performing procedures like gonioscopic assisted transluminal trabeculotomy in eyes with congenital glaucoma may be difficult many a times due to difficult visualization of angle structures. Inaccurate identification of the angle landmark may lead to various inadvertent surgical complications. Hence, there is a need for techniques to improve visualization of surgical landmarks during these procedures. In this study, 0.2% indocyanine green was used to stain the trabecular meshwork before the surgeon proceeded with gonioscopic assisted transluminal trabeculotomy. It yielded excellent differentiation of the trabecular meshwork by imparting a bright green hue. This led to successful identification of the site of incision and subsequent 360 degrees cannulation of Schlemm canal in 5/5 cases. Indocyanine green aided Schlemm canal identification is helpful in children with congenital glaucoma undergoing angle surgeries, especially in eyes with poor structure differentiation.